Systematic review of the association between dietary patterns and perinatal anxiety and depression - David Franciole Oliveira Silva; Ricardo Ney Cobucci; Ana Katherine Gonçalves; Severina Carla Vieira Cunha Lima (BMC, 2019)
Abstract Background Specific dietary factors contribute to greater risks of prenatal and postpartum anxiety and depression. This study aimed to systematically review and assess the evidence regarding the association between dietary patterns and perinatal anxiety and depression (PAAD). Methods A systematic search of the Latin American & Caribbean Health Sciences Literature (LILACS), PubMed, and Scopus databases for cross-sectional and cohort studies through April 2019 was conducted. The methodological quality of the studies was assessed using the Newcastle-Ottawa scale (NOS) and the Grading of Recommendations Assessment, Development and Evaluation (GRADE) framework was used to assess the quality of evidence. Results Ten studies (six cohort and four cross-sectional) were included. All studies had good methodological quality. In these studies, the Western (n = 10), healthy (n = 9), and traditional (n = 7) dietary patterns were examined. The healthy pattern was inversely associated with prenatal and postpartum anxiety and prenatal depression. The traditional Japanese dietary pattern, the traditional Indian-confinement dietary pattern, the United Kingdom traditional dietary and the traditional Brazilian dietary pattern were associated with a lower risk of prenatal depression, postpartum depression, prenatal anxiety and postpartum anxiety, respectively. There was no significant association between a Western dietary pattern and PAAD. The GRADE assessment suggested that the quality of the evidence was very low to low across all outcomes owing to the design, risk of bias, and small sample size. Conclusions There is no definitive evidence about the relationship between Western dietary patterns and perinatal anxiety and depression. However, it found an inverse association among the healthy dietary pattern and PAAD. Future studies will be required to better evaluate associations between meal patterns and PAAD. Such studies may provide new insights and assist in the development of new prevention and treatment strategies.